Ukraine’s European Integration and Its Current Challenges - Grіtsenko, Andriy; Borzenko - Slozko, Olena; Burlay, Tаtyana (Vilnius University Open Series, 2021)
The article shows the importance of Ukraine’s development within the framework of the European integration project. A positive impact of European integration on Ukraine’s development dynamics has been revealed. European integration accelerated after signing and implementing the European Union-Ukraine Association Agreement 2014. The main achievements of Ukraine’s European integration are related to the improvement of its institutions, as well as the growth of trade between Ukraine and the EU. It is found out the most serious challenges of European integration of Ukraine are related to the problems of economic growth, deindustrialization, foreign trade structural distortions, macro-financial stability, as well as the slowdown in a convergence between Ukraine and the EU. It is stated that Ukraine needs to restructure its national economy in line with the European and global context.
Keywords: economy; institutions; convergence; threats; EU enlargement